Neighborhood social environments, healthy resources, and adult diabetes: Accounting for activity space exposures. (January 2021) - Sharp, Gregory; Kimbro, Rachel Tolbert
Abstract: This study broadens contextual environments to include adults' activity spaces—inside and outside the residential neighborhood—to examine how contextual exposures shape type 2 diabetes risk. We use novel longitudinal data from the Los Angeles Family and Neighborhood Survey, construct time-weighted exposure measures of adults' social-structural and healthy resource environments, and execute random effects logistic models predicting the probability of being diabetic. Results indicate that residential and activity space exposures are independently associated with adult diabetes, and that residential and activity space healthy resources combine to influence diabetes risk in synergistic ways. Living in more socioeconomically advantaged neighborhoods reduces diabetes risk, particularly when spending time in activity spaces with greater access to recreational facilities. Moreover, healthier activity space environments may compensate for living in neighborhoods devoid of healthy food options to lessen diabetes risk. Adopting an activity space framework can inform multilevel interventions aimed at alleviating type 2 diabetes and other chronic ailments. Highlights: Residential and activity space exposures independently affect diabetes risk. Residential and activity space exposures combine to influence diabetes risk. Activity space recreational facilities benefit advantaged neighborhood residents. Activity space healthy outlets compensate for adults without local healthy options.